Knowledge and Attitudes of RN to BSN Students Before and After a Patient Safety Course. Issue 6 (November 2016) - Raines, Deborah A.; Grinslade, Susan; Fabry, Donna; Hewner, Sharon; Steeg, Linda
Abstract : Abstract: This pilot study evaluates the effectiveness of a stand-alone safety and quality improvement course and the integration of the Institute for Healthcare Improvement's safety modules into the RN to BSN program curriculum. A pre/postintervention design was used to measure the attitudes of a cohort of students. The results demonstrate gains in all dimensions measured, with statistically significant gains in four areas: safety general, team functioning, patient's role in error, and situational awareness. This study lends support to the value of a course focused on safety and quality and the use of the Institute for Healthcare Improvement modules in the curriculum